Bicycle trauma and alcohol intoxication. (December 2015) - Harada, Megan Y.; Gangi, Alexandra; Ko, Ara; Liou, Douglas Z.; Barmparas, Galinos; Li, Tong; Hotz, Heidi; Stewart, Donovan; Ley, Eric J.
Abstract: Introduction: As bicycling has become more popular, admissions after bicycle trauma are on the rise. The impact of alcohol use on bicycle trauma has not been well studied. The aim of this study was to examine the effect of alcohol intoxication on injury burden following bicycle-related crashes. Methods: A retrospective review of trauma patients presenting to a Level I trauma center after bicycle-related crashes from January 2002 to December 2011 was conducted. Demographics, injury data, alcohol intoxication, helmet use, and clinical outcomes were reviewed. Blood alcohol level (BAL) was considered positive if >0.01 g/dL. Variables were compared between patients based on BAL: negative, 0.01–0.16 g/dL, and >0.16 g/dL. Results: During the 10 year study period, 563 patients met study criteria; mean age was 33.5 ± 16.5 years, 87% were male, and mortality was 1%. On average, bicycle crashes increased over the study period by 4.4 collisions per year. BAL was tested in 211 (38%) patients. Mean BAL was 0.24 g/dL, with 37% of these patients being intoxicated (BAL ≥0.010 g/dL). Intoxicated patients were significantly less likely to wear a helmet (4.7% vs. 22.2%, p = 0.002) and to be involved in motor vehicle crash (59.0% vs. 81.2%, p < 0.001). There was no difference noted in the injury burden including ISS ≥16 (14.3% vs. 19.5%, p = 0.335) and AIS Head ≥3 (17.9% vs. 21.8%, p = 0.502). When comparing patients according to their BAL, there was a decreasing risk of motor vehicle collision with increasing BAL (81.2% for undetected, 76.5% for BAL ≤0.16 g/dL and 54.1% for BAL >0.16 g/dL, p < 0.001). The risk for a severe head injury (AIS Head ≥3) was significantly lower in helmeted patients (8.4% vs. 15.8%, p = 0.035). Conclusions: The incidence of bicycle-related crashes is increasing and more than a third of patients tested for alcohol after bicycle-related crashes are found to be intoxicated. The injury burden in intoxicated patients, including head trauma, was not different compared to non-intoxicated patients. In addition, the risk for a collision with a motor vehicle was significantly lower. Nonetheless, these patients rarely utilize a helmet. The findings from this study can be used for the development and implementation of preventive strategies to minimize the injury burden associated with bicycle crashes and intoxicated cyclists. Highlights: We examine the effect of alcohol intoxication on injury burden following bicycle-related crashes. The incidence of bicycle crashes is increasing and more than a 1/3 of injured patients screened for alcohol are intoxicated. Intoxicated cyclists are significantly less likely to wear a helmet and less likely to be involved in a motor vehicle crash. There is no difference in injury burden between intoxicated patients and non-intoxicated cyclists.